Impact of strategic options on improving organizational performance - A survey of the views of some administrative leaders in the Sudanese telecom companies - Ibrahim, Abdalrazig; Elmekki, Mohamed (Finance and Business Economies Review, 2019)
The world today is witnessing many changes, and on all levels, the gap between the form and the content of many phenomena that have a direct connection to the lives of individuals and organizations is growing day after day. In view of these sudden changes in the world, individuals must be able to make successful choices. Because these individuals have the wisdom and contact with individuals and organizations, this gives rise to the conviction that they are able to bridge and narrow this gap. This can only be achieved by adopting mature and optimal strategic options. The study problem focused on the fundamental question of whether the option The study aimed at defining the conceptual frameworks for each of the strategic options, performance, and related ideas that reinforce the leadership position in the research sample to make it a site for building the best strategic options instead of losing time in the details of daily work. , And the study reached a number of conclusions and recommendations.